Vasculitis in a patient with mixed cryoglobulinemia treated with rituximab biosimilar CT-P10: a case report. (2nd January 2020) - Vacchi, Caterina; Manfredi, Andreina; Salvarani, Carlo; Sebastiani, Marco
Abstract: Rituximab represents a milestone in the treatment of mixed cryoglobulinemic vasculitis. Despite usually well-tolerated, rituximab may induce different types of adverse drug reactions, including exacerbation of vasculitis. Rituximab biosimilar have been recently approved in Europe in the treatment of rheumatoid arthritis, but no data are available about effectiveness and safety of rituximab biosimilar in the treatment of mixed cryoglobulinemic vasculitis. We describe a severe skin vasculitis reactivation in a patient affected by rheumatoid arthritis and mixed cryoglobulinemic vasculitis treated with rituximab biosimilar. After 7 days from the first infusion, a severe purpuric rash at lower limbs appeared, that resolved in about 2 weeks with high dose-corticosteroid. Rituximab-induced vasculitis has also been described since 2001, but its pathophysiology is still controversial due to the anecdotical descriptions in literature and the variability of the time between the rituximab infusion and the onset of skin lesions. Up to date, this is the first report describing a vasculitic flare in a patient affected by mixed cryoglobulinemic vasculitis treated with rituximab biosimilar.